Tillage and N-source affect soil fertility, enzymatic activity, and crop yield in a maize–rice rotation system in the Indian Terai zone - Sahoo, Samaresh; Mukhopadhyay, Prabir; Mowrer, Jake; Maity, Pragati Pramanik; Maity, Aniruddha; Sinha, A.K.; Sow, Prodipto; Rakesh, S (Frontiers in Environmental Science, 2022)
A field experiment (2017–2019) was undertaken to study the short-term effects of tillage [zero tillage (ZT), conventional tillage (CT), and alternate tillage (AT)] and sources of organic and mineral fertilizer N [NS0—control, NS1—recommended doses of fertilizer (160:50:100), NS2—recommended level of fertilizer and crop residue (6 Mg·ha−1), NS3—75% of recommended N as fertilizer (120 kg·ha⁻1) and 25% N (40 kg·ha⁻1) as farm yard manure (FYM), and NS4—75% of recommended N as fertilizer and 25% N as vermicompost] on yield and soil quality under a maize–rice rotation system. Among N sources, NS4 produced the highest maize grain yield (10 Mg·ha⁻1). Residual effects of N sources on mean rice grain yield were evident only in crop residue (NS2)- and vermicompost (NS4)-treated plots. After the harvest of two complete maize–rice crop cycles, higher content of dehydrogenase activity (DHA) and urease activity (UR) were observed in the soil under AT as compared to ZT and CT at 0–10 cm (p < 0.05). Similarly, microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) also recorded positive changes at 0–10 cm soil depth, especially in NS2 and NS4 treatments. AT resulted in the highest total soil carbon (TOC) (8.10 g·kg−1), followed by CT (6.73 g·kg−1) and ZT (5.98 g·kg−1). Fertilizer N treatments, however, influenced the NO3-N accumulation beyond the root zone, where crop residue-based (NS2) fertilizer N treatment resulted in the highest NO3-N (32.52 kg·ha−1), and the lowest NO3-N (14.48 kg·ha−1) was observed in the FYM-based (NS3) treatment. Therefore, the practice of alternate tillage and integration of vermicompost (40 kg·N·ha−1) and chemical fertilizer (total 120 kg·ha−1) sources should be mostly recommended to farmers in the Terai region of India.